Relevance of small right-to-left shunt in contrast-enhanced transcranial Doppler in young and middle-aged patients with cryptogenic stroke: a report of two cases and literature review. (17th October 2022) - Cao, Liming; Huang, Xuming; Wang, Huilan
Abstract: Aim: The clinical relevance of small right-to-left shunt (RLS) in young patients with cryptogenic stroke is unknown. We aimed to analyze and understand the relationship between cryptogenic stroke and small RLS by studying specific cases. Materials and methods: Clinical data from two cases of small RLS-related cryptogenic stroke in young patients were collected prospectively and analyzed. We followed up the patients for >1 year after discharge. Results: Case 1 . A 50-year-old man was admitted for slurred speech and right hemiplegia and was diagnosed with acute cerebral infarction. Contrast-enhanced transcranial Doppler (c-TCD) and contrast-enhanced transthoracic echocardiography (c-TTE) revealed a microbubble and 20–30 microbubbles per section, respectively, in the resting state. Three months later, he was readmitted for stroke recurrence. Transesophageal echocardiography (TEE) confirmed a patent foramen ovale (PFO), and he underwent transcatheter closure of the PFO. Case 2 . A 48-year-old man was admitted for right hemiplegia with slurred speech. Brain magnetic resonance imaging showed acute cerebral infarction. c-TCD and contrast-enhanced TEE (c-TEE) revealed <10 microbubbles and approximately 20 microbubbles per section, respectively. These findings suggested a PFO. Two months later, he was readmitted for stroke recurrence. He underwent transcatheter closure of the PFO. Follow-up of cases 1 and 2 at >1 and >1.5 years after discharge, respectively, showed no stroke recurrence. Conclusion: We suspected that a small RLS may cause cryptogenic stroke. A small RLS in c-TCD in stroke patients may not be actually small, and c-TEE/c-TTE may be valuable in finding larger RLSs.